Response to "What do Klein et al. tell us about test scores in Texas?" - Klein, Stephen P.; Hamilton, Laura S.; McCaffrey, Daniel F.; Stecher, Brian M. (Education Policy Analysis Archives, 2005)
Wherein the authors reply to Toenjes, Vol. 13 No. 36 "What do Klein et al. tell us about test scores in Texas?"